The Dynamics of Learning Engagement in Challenge-Based Online Learning - Ifenthaler, D.; Gibson, David; Zheng, L. (IEEE, 2018)
Vast amounts of educational data created by learners interacting with digital learning tools open up the opportunity to gain insights for improving education at a new level of evidence-based research into learning and teaching. This study is part of a research programme investigating the dynamics and impacts of learning engagement in a challenge-based online learning environment. Learning engagement is a multidimensional concept which includes an individual’s ability to behaviourally, cognitively, emotionally, and motivationally engage in an on-going learning process. Challenge-based learning gives significant freedom to the learner to decide what and when to engage and interact with digital learning materials. In light of previous empirical findings, we expect that learning engagement is positively related to learning performance in a challenge-based online learning environment. This study was based on data from the Careers Challenge platform, including transaction data from 8,951 students. Findings indicate that learning engagement in challenge-based online learning environments is, as expected, positively related to learning performance. Implications point toward the need for personalised and adaptive learning environments to be developed in order to cater for the individual needs of learners in challenge-based online learning environments.